EKO-REGIONAL: Jurnal Pembangunan Ekonomi Wilayah 2022
DOI: 10.32424/1.erjpe.2022.17.2.3167
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Information and Communication Technology Sector Development in Java Island, 2016-2020

Abstract: The Information and Communication Technology (ICT) sector is one of the main drivers of economic growth, so the condition of the ICT sector becomes an essential factor in development. The ICT sector consists of the manufacturing and service sectors whose main activities are related to the development, production, commercial and intensive use of ICT. In 2016-2020, six provinces on Pulau Jawa became the provinces with the highest IP-ICT scores. Pulau Jawa had a GDP share of 59 percent of Indonesia's GDP in 2020.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
0
0
Order By: Relevance
“…Apart from that, the average expenditure on ICT in Bali Province is quite low, ranging between 123 -172 thousand rupiah from 2016 to 2021. Following the research of Dharmawan [6] and Triana [11] which concluded that the consumption behavior shown through the average consumption for ICT does not show a significant difference so that the average household consumption for ICT is unable to explain the diversity of GRDP ICT sector. This result is also in concert with research conducted by Martaningsih and Marhaeni (in [21]) which shows that household consumption expenditure has no effect on economic growth in the districts/cities of the Bali Province.…”
Section: Variables Affecting the Development Of Grdp In The Ict Sectormentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from that, the average expenditure on ICT in Bali Province is quite low, ranging between 123 -172 thousand rupiah from 2016 to 2021. Following the research of Dharmawan [6] and Triana [11] which concluded that the consumption behavior shown through the average consumption for ICT does not show a significant difference so that the average household consumption for ICT is unable to explain the diversity of GRDP ICT sector. This result is also in concert with research conducted by Martaningsih and Marhaeni (in [21]) which shows that household consumption expenditure has no effect on economic growth in the districts/cities of the Bali Province.…”
Section: Variables Affecting the Development Of Grdp In The Ict Sectormentioning
confidence: 99%
“…Research by Dharmawan (in [6]) shows that the percentage of the population who own cell phones has proven to affect the growth of the ICT sector in Indonesia. Meanwhile, Triana's research (in [11]) shows that the growth of the ICT sector is influenced by the number of workers in the ICT sector, the average length of schooling, and internet usage. Consequently, ICT plays an important role as a vehicle for economic growth [12].…”
Section: Introductionmentioning
confidence: 99%